(untitled) (Revista Brasileira Multidisciplinar, 2025)
Bloodstream infections (BSI) are a major problem in intensive care units (ICUs), with increasing rates despite medical advancements. These infections are closely tied to patient deaths and are influenced by various risk factors identified through ICU research. Infections caused by antibiotic-resistant Gram-negative bacilli (GNBs) negatively impact patients, especially in underdeveloped countries like Brazil. This study investigated nosocomial BSI caused by GNB among ICU patients at Federal University of Uberlândia between 2012 and 2014. The research focused on understanding the epidemiology of these infections, their effect on mortality rates, and the corresponding risk factors involved. In a three-year study, 110 nosocomial bloodstream infections were caused by GNB, mainly from the lower respiratory tract (70.9%) with the Enterobacteriaceae family corresponding to 58.3% of the episodes. Klebsiella pneumoniae (20.9%), Acinetobacter baumannii (20.0%) and Pseudomonas aeruginosa (19.1%) were the most frequent microorganisms. In our cohort, the overall mortality rate was of 39.5%, with 45.4% attributed to patients presenting GNB infections, especially multidrug resistant (MDR) organisms. This study revealed that septic shock and mechanical ventilation were significant mortality risk factors. Notably, patients with BSI caused by GNB, particularly MDR strains, experienced a faster progression towards death within the initial 20 days of hospitalization compared to those with infections from different microorganisms.